POTENSI HIDROKARBON ENDAPAN SYN-RIFT DENGAN PENDEKATAN PASIF SEISMIK PADA CEKUNGAN OMBILIN - Habrianta, Litto
Ombilin Basin is known with good hydrocarbon potential and prospects. In terms of petroleum system, study area has all of petroleum system running aspects. It is characterized by oil seeps occurrence into the surface. Geological conditions are complicated due to tectonics in Ombilin Basin make some previous exploration was failed to find economic quantities of hydrocarbons. Passive seismic method is the development of instrumentation technology (ultra high broadband seismometer sensitivity) for hydrocarbon exploration objectives. This method can detect very weak acoustic signals (micro-acoustic) and very low frequency (infrasound). This method is started with interesting phenomenon, microseismic signal is detected above on hydrocarbon reservoir. Based on this discovery, it is developed into a technology to detect hydrocarbons which can be used directly i on exploration, field development, as well as in oil and gas field monitoring. On techtonostratigraphy process, Ombilin Basin is a half graben basin which is composed by pre-rift of igneous and metamorphic rocks of Tuhur Formation and Silungkang Formation, syn-rift of Sangkarewang Formation, Brani Formation, Sawahtambang Formation and Sawahlunto Formation, and post-rift form Ombilin Formation and Ranau Formation. In petroleum system, good source is derived by Sangkarewang Formation and Coal in Sawahlunto Formation. While acts as reservoir is Sawahlunto Formation and Sawahtambang Formation with cap rock is Ombilin Formation. Based on Profile of Sinamar-1 Well Analysis, it indicated that source rock has reached peak of maturity. It is caused by Sinamar-1 Well is located on deep area of Ombilin Basin. Paleography condition of Ombilin Basin is obtained from Isopach Map of Sawahtambang Formation - Sangkarewang Formation. From this maps it can estimated the direction of hydrocarbon migration which generally trend is South - Southeast. It is indicated by oil seepage emergence on surface. Passive Seismic methods approaching was obtained that Power Spectral Density Mean at non potential area is 1.5631 x 10-6 dB and 2.5314 x 10-6 dB at Sinamar-1 Well which are on prospect area (22 BOPD, 13:56 MMCFD, 314 BCPD ). Based on anomaly mean value distribution, Power Spectral Density distribution more greater on south - southeast. This pattern indicates that hydrocarbon potential more better into South-East direction in accordance with migration trend of hydrocarbons in accordance with petroleum system analysis of Ombilin Basin.